(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This investigation is conducted to estimate the dispersion phenomena for selected sites in Babylon governorate (ALkheder – Almossiab, ALsadda, ALbunafaa, ALhashmia,). The main aim of this investigation is to study dispersion phenomena, and identification and classification of soils to (high, intermediate, and non-dispersion) depending on special test methods in dispersion phenomena. The experimental tests that were done; indexes, physical, and chemical tests to natural soils and special tests were done to the identification and classification of dispersion soils. The results of crumb test showed weak dispersion (Grade 2) for AL sadda soil, but the soils of ((ALkhezer – Almossaab, AL.bunafaa, AL.hashmia) showed intermediate dispersion (Grade 3). The results of the double hydrometer test showed that ALkheder – Al.mossaab, and ALbunafaa were of intermediate dispersion soils, and for AL.hashmia, and AL sadda soils were non – dispersive. The results of slacking test indicated that (ALkheder - Almossaab, ALbunafeej) were dispersive soils and (AL.hashmia, ALsadda soils) were non– dispersive. While the results of soluble salts in pore water test indicated that all soils were non–dispersive but with different ratios according to its position in zone B of the classification chart.